Development of Performance Measurement Framework for Supply Chain in Desalination Industry using AHP - M. Nopiah, Zulkifli; Balfaqih, Hasan; Saibani, Nizaroyani (International Journal of Engineering and Technology, 2018)
The concern regarding desalination technology has been rising gradually for the last years because of the enlarged need for drinkable water worldwide. Yet, there are not many studies concerned assessing the seawater desalination supply chain (WDSC) from end to end. Therefore, the objective of this paper is to propose a framework which is intended to assess the performance of WDSC. Different desalination and supply chain performance criteria and metrics have been revised and distributed into financial, social, operation, and environmental perspective. The performance criteria and metrics have been further revised by a panel of experts using Delphi-AHP technique. A weight factor has been allocated to every perspective, criteria and metric based on its importance to the WDSC. The proposed framework could serve as a reference for the researchers in desalination industry. The proposed framework would be helpful for both academics and practitioners.Â